"Journal: 100 Years / MILITARY ENGINEERING (Part IV) Mining and Demolitions General Staff, Ware Office, 1910 London" - Robert Hopler (International Society of Explosives Engineers, 2011)
209. Nitro-glycerine is produced by the action of nitric and sulphuric acids on glycerine, and is a heavy liquid of oily appearance, of specific gravity about 1•6, varying from colourless when quite pure to a yellow or brownish yellow. It is of a very sweet taste, and without odour, and is an active poison. Mere handling of it will in most persons induce sickness and headache. It explodes when heated to about 360° F. or from shock, but in small quantities it ignites and burns with some difficulty by the mere contact of flame.